2011
DOI: 10.1166/jnn.2011.3560
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water Soluble Quantum Dots for Monitoring Carrier-DNA Nanoparticles in Plant Cells

Abstract: Fluorescent quantum dots (QDs) have shown great promise for use as biolabels in cell and animal biology and more recently in plant sciences. An important use of QDs is for monitoring the dynamics, intracellular trafficking, and fate of carrier-DNA nanocomplexes in cell transfection and potentially in plant transformation. In this study, a low cost aqueous procedure has been developed to efficiently prepare biocompatible QDs for monitoring nanoparticle-mediated gene transfer in conjunction with molecular breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…To date, nanoparticle‐mediated delivery of biogenic molecules to plant cells has been limited to nucleic acids, including double or single stranded DNA3, 24–28 and small interfering RNA 29. Delivery and release of chemical substances such as phenanthrene and plant growth regulators have also been reported 30, 31.…”
Section: Introductionmentioning
confidence: 99%
“…To date, nanoparticle‐mediated delivery of biogenic molecules to plant cells has been limited to nucleic acids, including double or single stranded DNA3, 24–28 and small interfering RNA 29. Delivery and release of chemical substances such as phenanthrene and plant growth regulators have also been reported 30, 31.…”
Section: Introductionmentioning
confidence: 99%
“…However, protoplast-based transformation methods hold disadvantages in that the viability of the protoplasts and their ability to divide are strongly reduced by the chemicals that are applied to disorganize the cell wall. For this reason, recent studies have focused on intact plant cells; it was found to that they are able to achieve endocytosis to directly internalize single-walled carbon nanotubes (CNTs), CdSe/ZnS QDs, or poly (amidoamine) dendrimer from the extracellular environment [14][15][16][17][18]. Other work showed that multi-walled CNTs with attached cellulose are also able to penetrate the cell wall, and transport intracellularly through cellulose-inducing nanoholes [19].…”
mentioning
confidence: 99%
“…It has been modifi ed into octapeptide having a condense DNA with high transfection effi ciencies and lower toxicity compared with non-modifi ed chitosan. The integration of DNA through Jatropha curcas cells has been studied through this type of nanoparticles (Wang et al 2011 ) (Table 1 ).…”
Section: Precision Farming and Crop Improvement Via Nanotechnologymentioning
confidence: 99%